Revision of the Mexican and Central American species of Mortoniella (Trichoptera: Glossosomatidae: Protoptilinae) - Blahnik, Roger J.; Holzenthal, Ralph W. (Zootaxa, 2008)
The genus Mexitrichia Mosely, 1937 (27 described species) is synonymized with Mortoniella Ulmer, 1906 (22 described species) and a revised generic description is provided for the genus. These species are placed in 4 recognized species groups. Mexican and Central American species of Mortoniella are revised to include 6 species formerly placed in Mexitrichia and 22 new species from Costa Rica, Panama, and Mexico. New species combinations for these regional species include: Mortoniella florica (Flint, 1974), M. leroda (Mosely, 1937), M. meralda (Mosely, 1954), M. pacuara (Flint, 1974), M. rancura (Mosely, 1954), and M. rovira (Flint, 1974). New species of Mortoniella described here (followed by the country of provenance) include M. akantha (Costa Rica) M. anakantha (Costa Rica) M. aviceps (Costa Rica, Panama) M. brachyrhachos (Mexico), M. buenoi (Mexico), M. carinula (Costa Rica), M. caudicula (Costa Rica), M. falcicula (Mexico), M. mexicana (Mexico) M. munozi (Costa Rica, Panama), M. opinionis (Costa Rica), M. panamensis (Panama), M. papillata (Costa Rica), M. pectinella (Panama), M. propinqua (Costa Rica), M. redunca (Costa Rica), M. rodmani (Costa Rica), M. sicula (Costa Rica), M. stilula (Costa Rica), M. tapanti (Costa Rica, Panama), M. taurina (Costa Rica, Panama), and M. umbonata (Panama). Males of all known Mexican and Central American species are illustrated or reillustrated and a key is provided for males of the species.